2012
DOI: 10.1038/jhg.2012.5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of inositol 1, 4, 5-triphosphate receptor type 1 gene deletion, the mutation for spinocerebellar ataxia type 15, in Japan screened by gene dosage

Abstract: Spinocerebellar ataxia type 15 (SCA15) is an autosomal dominant neurodegenerative disorder clinically characterized by late-onset, slowly progressive pure cerebellar ataxia. This disease is caused by a heterozygous deletion of the inositol 1, 4, 5-triphosphate receptor type 1 (ITPR1) gene, suggesting that haploinsufficiency of the receptor function is the plausible disease mechanism. To clarify the prevalence of SCA15 in Japan, we designed four sets of probes and primers in different regions of ITPR1 and perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…These index patients were all excluded for previously known SCA mutations, which accounted for about 50% of all SCAs in their cohorts 1 11–13. All patients were collected from diverse areas of their respective countries: Pitié-Salpêtrière University Hospital and through the SPATAX network (France; http://spatax.wordpress.com/), Ludwig-Maximilians-University Munich (Germany), University of Tübingen (Germany) and Tokyo Medical and Dental University (Japan) 12. A half of the Japanese SCA cohort was collected from the Tokyo Metropolitan area, and thus the present Japanese cohort is based on a population distinct from the previous studies 4 6.…”
Section: Methodsmentioning
confidence: 99%
“…These index patients were all excluded for previously known SCA mutations, which accounted for about 50% of all SCAs in their cohorts 1 11–13. All patients were collected from diverse areas of their respective countries: Pitié-Salpêtrière University Hospital and through the SPATAX network (France; http://spatax.wordpress.com/), Ludwig-Maximilians-University Munich (Germany), University of Tübingen (Germany) and Tokyo Medical and Dental University (Japan) 12. A half of the Japanese SCA cohort was collected from the Tokyo Metropolitan area, and thus the present Japanese cohort is based on a population distinct from the previous studies 4 6.…”
Section: Methodsmentioning
confidence: 99%
“…Most IP 3 R1 LBD mutations lead to diseases characterized by early-onset, non-progressive ataxia; however, one identified mutation, V494I, has been associated with the late-onset, slowly progressive spinocerebellar atrophy (SCA15; MIM #606658) (Ganesamoorthy et al, 2009). Although generally the result of large, heterozygous deletions of ITPR1 , SCA-15 associated missense mutations have also been identified in the LBD and regulatory domain (Di Gregorio et al, 2010, Hara et al, 2008, Iwaki et al, 2008, Marelli et al, 2011, Novak et al, 2010, Obayashi et al, 2012, van de Leemput et al, 2007, Yamazaki et al, 2011, Ganesamoorthy et al, 2009). While the suspected mechanism of the autosomal dominant deletions is haploinsufficiency, the mechanism of action of SCA15-assocaited missense mutations is not as clear (Hara et al, 2008, Yamazaki et al, 2011, Ganesamoorthy et al, 2009).…”
Section: Ip3r Mutations Associated With Human Disease By Domain: Mutamentioning
confidence: 99%
“…Although these families also have a partial deletion of a neighboring gene encoding SUMF1 (sulfatase-modifying factor 1), a subsequent study reported only a heterozygous deletion of exons 1-48 of the ITPR1 gene, but not of SUMF1, in a patient with SCA16 (Iwaki et al 2008), supporting the idea that haploinsufficiency of ITPR1 is a cause for SCA15/16. Thereafter, the deletion of the ITPR1 gene has been reported in many SCA15/16 families Marelli et al 2011;Obayashi et al 2012;Novak et al 2010).…”
Section: Ip 3 R1 and Brain Diseasementioning
confidence: 99%